Approaches Mediating Oxytocin Regulation of the Immune System - Li, Tong; Wang, Ping; Wang, Stephani C.; Wang, Yu-Feng (Frontiers in Immunology, 2017)
The hypothalamic neuroendocrine system is mainly composed of the neural structures regulating hormone secretion from the pituitary gland and has been considered as the higher regulatory center of the immune system. Recently, the hypothalamo- neurohypophysial system (HNS) emerged as an important component of neuroendocrine-immune network wherein the oxytocin (OT)-secreting system (OSS) plays an essential role. The OSS, consisting of OT neurons in the supraoptic nucleus, paraventricular nucleus and their several accessory nuclei and associated structures, can integrate neural, endocrine, metabolic and immune information and plays a pivotal role in the development and functions of the immune system. The OSS can promote the development of thymus and bone marrow, perform immune surveillance, strengthen immune defense, and maintain immune homeostasis. Correspondingly, OT can inhibit inflammation, exert antibiotic-like effect, promote wound healing and regeneration, and suppress stress-associated immune disorders. In this process, the OSS can release OT to act on immune system directly by activating OT receptors or through modulating activities of other hypothalamic-pituitary-immune axes and autonomic nervous system indirectly. However, our understandings of the role of the OSS in neuroendocrine regulation of immune system are largely incomplete, particularly about its relationship with other hypothalamic- pituitary-immune axes and the vasopressin-secreting system that coexists with the OSS in the HNS. In addition, it remains unclear about the relationship between the OSS and peripherally produced OT in immune regulation, particularly intrathymic OT that is known to elicit central immunological self-tolerance of T-cells to hypophysial hormones. In this work, we provide a brief review of current knowledge of the features of OSS regulation of immune system and of potential approaches that mediate OSS coordination of the activities of entire neuroendocrine-immune network.